Potential role of JAK-STAT signaling pathway in the neurogenic-to-gliogenic shift in down syndrome brain - Lee, Han Chung; Tan, Kai Leng; Cheah, Pike See; Ling, King Hwa (Hindawi Publishing Corporation, 2016)
Trisomy of human chromosome 21 in Down syndrome (DS) leads to several phenotypes, such as mild-to-severe intellectual disability, hypotonia, and craniofacial dysmorphisms. These are fundamental hallmarks of the disorder that affect the quality of life of most individuals with DS. Proper brain development involves meticulous regulation of various signaling pathways, and dysregulation may result in abnormal neurodevelopment. DS brain is characterized by an increased number of astrocytes with reduced number of neurons. In mouse models for DS, the pool of neural progenitor cells commits to glia rather than neuronal cell fate in the DS brain. However, the mechanism(s) and consequences of this slight neurogenic-to-gliogenic shift in DS brain are still poorly understood. To date, Janus kinase-signal transducer and activator of transcription (JAK-STAT) signaling has been proposed to be crucial in various developmental pathways, especially in promoting astrogliogenesis. Since both human and mouse models of DS brain exhibit less neurons and a higher percentage of cells with astrocytic phenotypes, understanding the role of JAK-STAT signaling in DS brain development will provide novel insight into its role in the pathogenesis of DS brain and may serve as a potential target for the development of effective therapy to improve DS cognition.